Well-crystallized mesoporous samaria-doped ceria from EDTA-citrate complexing process with in situ created NiO as recyclable template - Ran, R.; Guo, Y.; Zheng, Y.; Wang, K.; Shao, Zongping (Elsevier B.V., 2010)
A facile EDTA-citrate complexing process with in situ created recyclable NiO as inorganic template was developed for the synthesis of mesoporous samaria-doped ceria (SDC) at high temperatures. By applying metal nitrates as the raw materials for the cation sources and EDTA and citric acid as the chelants, the molecular-level homogeneous mixing of the metal ions was successfully preserved to the solid precursor. Low-temperature calcination resulted in the formation of mixture oxides of nano-size SDC and NiO oxides, as demonstrated by XRD, FT-IR and BET analysis. A possible mechanism for the formation of mesoporous SDC was proposed, in which the SDC particles surrounded the nano-size NiO grains and sintered during the high-temperature calcination. Dissolving the coated NiO in SDC and self-aggregated NiO particulates from the mixture with diluted HNO3 resulted in a porous pure-phase SDC oxide. At optimal SDC to NiO ratios, mesoporous, thermally stable and well-crystallized SDC powder with narrow pore size distribution and high surface area was synthesized. © 2009 Elsevier B.V. All rights reserved.